Phraseme Constructions: Productivity and Creativity (with Russian Examples) - Anna Pavlova (Linguistische Treffen in Wrocław, 2025)
This paper explores the productivity and creativity of phraseme constructions (PhraCons) within the framework of Construction Grammar, with a particular focus on Russian examples. Productivity, defined as the diversity of slot fillers, and creativity, the speaker’s ability to generate novel constructs, are studied in tandem to understand their interrelation. By examining the interplay between productivity and creativity, the study expands the theoretical understanding of Construction Grammar, particularly with respect to idiomatic and schematic constructions. The study is part of the ongoing COST-project “PhraConRep,” aimed at documenting phraseme constructions across Eastern and Central European languages. This research contributes to the development of multilingual repositories for phraseme constructions, enriching cross-linguistic studies. The primary goal is to classify PhraCons based on their productivity levels and to analyze how their flexibility impacts linguistic creativity. The research addresses key questions about the boundaries between theoretically productive and practically utilized constructions. The analysis uses corpus data from Russian and multilingual sources, categorizing constructions based on their productivity, type frequency, and semantic diversity. Slot fillers are evaluated to determine the degree of creativity and freedom speakers have when using these constructions. The study identifies a continuum of productivity levels, ranging from highly productive to non-productive PhraCons. It demonstrates that creativity often involves the use of rare slot fillers, with less frequent constructions sometimes requiring greater inventive effort. The research also highlights the role of idiomaticity and schema flexibility in fostering linguistic innovation. The paper argues that productivity and creativity are gradient properties, influencing not only the flexibility of constructions but also their lexicalization in discourse. These findings have implications for both theoretical linguistics and practical lexicography. Insights from this study support the creation of multilingual PhraCons repositories, providing tools for language teaching, translation, and lexicographical endeavors.